1998
DOI: 10.1116/1.590007
|View full text |Cite
|
Sign up to set email alerts
|

Residence time effects on SiO2/Si selective etching employing high density fluorocarbon plasma

Abstract: Articles you may be interested inSurface kinetics modeling of silicon and silicon oxide plasma etching. I. Effect of neutral and ion fluxes on etching yield of silicon oxide in fluorocarbon plasmas Effect of nonsinusoidal bias waveforms on ion energy distributions and fluorocarbon plasma etch selectivityThe residence time effects on SiO 2 etching characteristics using inductively coupled plasma of C 4 F 8 alone were first studied in the range from 6 to 300 ms. It was then found that SiO 2 and Si etch rates wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The substitution of Ar is also known to help suppress excessive polymerization and improve etch rate by higher ion density. 10 It reveals a monotonic increase of ion density for the Ar percentage and shows a rapid increase near the 70% range. To avoid an abrupt increase of ion density, we chose a condition of 60% Ar to check the frequency dependence of ion density.…”
Section: Resultsmentioning
confidence: 91%
“…The substitution of Ar is also known to help suppress excessive polymerization and improve etch rate by higher ion density. 10 It reveals a monotonic increase of ion density for the Ar percentage and shows a rapid increase near the 70% range. To avoid an abrupt increase of ion density, we chose a condition of 60% Ar to check the frequency dependence of ion density.…”
Section: Resultsmentioning
confidence: 91%
“…As a result, the plasma species densities changed with the residence time, as observed in Ref. [19]. In addition, the density profile alters when changing the gap between the electrodes due to the competition of the above time scales, [20] or by considering a gas flow module into the fluid model or not, [21] in a capacitively coupled plasma source.…”
Section: Introductionmentioning
confidence: 72%
“…10 above. The fact that several experimental works revealed that the CF þ ions are the most predominant ions in the C 4 F 8 ICP source 25,57,58 and that both our hybrid model with relatively simple surface kinetics, as well as the global model with more complete polymer surface kinetics, fail to predict this higher CF þ ion density, indicates that some mechanisms for the formation of CF þ ions are still missing from both models. It is not yet clear which mechanisms are missing, but some candidates might be the direct production of CF þ ions by ion bombardment on the surface polymer, or bulk dissociative charge exchange of ions with polymeric heavy fc neutrals.…”
Section: Validation and Limitations Of The Modelmentioning
confidence: 92%